Vibrant Architecture. Matter as a CoDesigner of Living Structures (2015)
Nearly 50 years had passed for Yomo Yanobe since the last tsunami devastated the Sendai region. He was a young rescue volunteer in the clean-up operation after the 2011 events. It was almost unthinkable that he would find himself facing the same situation that had shaped his life. Back then, his youthful indifference to mortality had spared him a little from the full emotional impact of the tragedy. Yet he had been deeply affected by the experience. Yomo had not rescued a single person in two whole weeks of searching, and he could not shake the feeling that someone was still buried under rubble, waiting to be found. Over the intervening decades he suffered many sleepless nights wrestling with the bitter guilt of a survivor. At night it twisted and clawed its way into his dreams, and during the day it taunted him with a profound sense of uselessness So, when the early-warning systems and media channels screamed that a devastating earthquake had just struck the north-eastern region again, reaching a shocking 9.2 magnitude, Yomo knew that a swell of tsunami white water would gluttonously churn its way inland to engulf its prey. He wanted to resume his rescue duties, even after this long intermission. He hoped it would be different this time. Maybe he could save someone.